Assessment of Neutrophil Chemotaxis, Phagocytosis and Specific Granule Release in Aggressive and Chronic Periodontitis Patients: An In-Vitro Study - Priyanka M Agrawal; Chanchal S Bherwani; Dnyaneshwari Gujar; Amit P Thareja; Nilima M Landge; Darshana Dalaya; Setu Mathur; Amit Chaudhari (RUHS Journal of Health Sciences, 2023)
Introduction: Neutrophils are responsible for immunologically induced tissue injury. When normal regulatory mechanisms fail, following activation by bacterial by-products or other immune stimuli, neutrophils execute several specialized functions that include chemotaxis, phagocytosis, generation of reactive oxygen metabolites and specific granule release. The important role polymorphonuclear neutrophils (PMNs) play in optimal functioning of the immune defense system has led to speculation that a partly compromised system could severely weaken the defense mounted against a bacterial insult and permit the occurrence and progression of infections. The study was aimed to assess neutrophil function i.e. chemotaxis, phagocytosis and specific granule release in patients with aggressive and chronic periodontitis in Indian population. Methodology: 60 patients with age group varying between 13-60 years from both sex were selected and were divided into three groups: Group I — 20 Generalized Aggressive Periodontitis subjects (GAgP), Group II — 20 Generalized Chronic Periodontitis subjects (CP), Group III — 20 Control Group of periodontally healthy subjects. Venous blood samples were collected and various neutrophil functions viz. chemotaxis, phagocytosis and specific granule release were carried out using different assays such as N-Formylmethionyl-leucyl-phenylalanine (FMLP), Candidia albicans suspension, Nitroblue tetrazolium test (NBT). Results: The results of the study suggest that chemotaxis was significantly reduced in generalised aggressive periodontitis patients as compared to chronic periodontitis and periodontally healthy subjects. GAgP and CP patients showed no significant difference in phagocytosis rate as compared to periodontally healthy control group. Unstimulated NBT reduction is increased in neutrophils from patients with infection and the intracellular killing capacity of neutrophils is reduced in GAgP and CP patients. Conclusion: The assessment of neutrophil fu